Pengaruh Project Based Learning terhadap Keterampilan Menulis Deskripsi - Rahmawati, Deviana; Bintang Aji Pradana, Agrissto; Meinita Triana, Putri (Universitas Muhammadiyah Magelang, 2026)
This study was conducted to test the impact of implementing the Project-Based Learning (PjBL) model on the descriptive writing skills of fourth-grade students at Keji 2 Public Elementary School. A quasi-experimental design (QoD) with a Non-Equivalent Control Group Design was employed. The study involved 44 fourth-grade students, divided equally into an experimental group (22 students) and a control group (22 students). Data were collected through performance tests and processed using SPSS version 25 for Windows. Due to the non-normal distribution of the data, prerequisite tests used non-parametric Wilcoxon analysis and Levene's homogeneity test, while hypotheses were tested using the Mann-Whitney test. The research findings demonstrate that the PjBL model significantly impacts students' descriptive writing skills. This is demonstrated by the Mann-Whitney test significance value of 0.000 (p < 0.05). Empirically, the improvement is evident from the shift in average scores: the experimental group's score increased from 49 (pretest) to 81 (posttest), while the control group's score increased from 38 (pretest) to 61 (posttest). This contrasting difference in achievement confirms that the implementation of the Project-Based Learning model is effective in improving the descriptive writing skills of fourth-grade students.